A Phase I Comparative Pharmacokinetic and Safety Study of Two Intravenous Formulations of Vinorelbine in Patients With Advanced Non-Small Cell Lung Cancer - Wu, Guolan; Wu, Lihua; Zhou, Huili; Lin, Meihua; Peng, Ling; Wang, Yina; Zhai, You; Hu, Xingjiang; Zheng, Yunliang; Lv, Duo; Liu, Jian; Shentu, Jianzhong (Frontiers in Pharmacology, 2019)
Purpose: The aim of this study was to compare the pharmacokinetics and safety between two vinorelbine formulations (a new oil-in-water emulsion formulation (ANX) versus a previously marketed solution formulation (Navelbine)) in Chinese patients with advanced non-small cell lung cancer (NSCLC). Method: This was a single-center, randomized, open-label study. Eligible patients aged 18-70 years who had histologically or cytologically confirmed NSCLC were enrolled. In cycle 1, the patients alternatively received the two formulations (30 mg/m2, given as a 10-minute infusion) with a 7-day interval. Samples for pharmacokinetic analysis were taken during cycle 1. For all subsequent 21-day cycles (maximum 4 cycles), ANX was administered on days 1 and day 8. Bioequivalence analysis was performed on Cmax, AUClast and AUCinf. The safety profiles and anti-tumor effects were also determined. Results: From March 2013 to January 2015, 24 patients were enrolled and 20 were eligible for pharmacokinetic evaluation. The 20 subjects in the pharmacokinetic analysis set had a median age of 61 years (range 37-70 years), and 15 patients were male (75%). Mean vinorelbine Cmax values for ANX and Navelbine were 1317.40 and 1446.30 ng/mL, respectively. Corresponding AUClast values were 797.08 and 924.26 ng•h/mL, respectively. AUCinf values were 830.14 and 957.16 ng•h/mL, respectively. Treatment ratios of the geometric means were 90.00% (90% CI, 83.22% - 99.07%) for Cmax, 86.92%（90% CI ,80.91% - 93.37%）for AUClast, and 87.44% (90% CI 82.08% - 93.16%) for AUCinf. These results met the required 80% to 125% bioequivalence criteria. The most frequently reported adverse events after vinorelbine administration were neutropenia, leucopenia, neutropenic fever and constipation. Conclusion: At therapeutic dosage levels, pharmacokinetic behavior and safety profiles were similar for both formulations. Chinese National Registry Code: ChiCTR-IPR-15005856.